2016
DOI: 10.3389/fpls.2016.00001
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses Provide Novel Insights into Plant Growth and Ginsenoside Biosynthesis in Forest Cultivated Panax ginseng (F. Ginseng)

Abstract: F. Ginseng (Panax ginseng) is planted in the forest to enhance the natural ginseng resources, which have an immense medicinal and economic value. The morphology of the cultivated plants becomes similar to that of wild growing ginseng (W. Ginseng) over the years. So far, there have been no studies highlighting the physiological or functional changes in F. Ginseng and its wild counterparts. In the present study, we used proteomic technologies (2DE and iTRAQ) coupled to mass spectrometry to compare W. Ginseng and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
844
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 496 publications
(905 citation statements)
references
References 85 publications
55
844
6
Order By: Relevance
“…The success of gene expression quantification via the RT-qPCR approach is however, entirely dependant upon the identification and use of a group of suitable reference genes for expression normalisation due to; (1) there not being any ‘universal’ reference gene(s) available for use across a wide range of phenotypically distinct plant species or experimental conditions in a single species [23, 24], and; (2) the use of only a single reference gene could lead to an incorrect functional interpretation of the expression profile of a gene [18, 21]. Fang et al [18] specify that an appropriate reference gene is an endogenous gene that exhibits relatively stable expression across a group of biological samples, including different cell or tissue types, different stages of development, or a range of experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The success of gene expression quantification via the RT-qPCR approach is however, entirely dependant upon the identification and use of a group of suitable reference genes for expression normalisation due to; (1) there not being any ‘universal’ reference gene(s) available for use across a wide range of phenotypically distinct plant species or experimental conditions in a single species [23, 24], and; (2) the use of only a single reference gene could lead to an incorrect functional interpretation of the expression profile of a gene [18, 21]. Fang et al [18] specify that an appropriate reference gene is an endogenous gene that exhibits relatively stable expression across a group of biological samples, including different cell or tissue types, different stages of development, or a range of experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Stomata are the main structures responsible for leaf gaseous exchange, salinity restricts the availability of atmospheric CO 2 due to stomatal closure, and consequently, the consumption of NADPH is reduced in Calvin cycle. The over‐reduction in ferredoxin in photosystem I leads to the production of oxygen radicals, which causes a chain reaction of singlet oxygen species (ROS) in a process called Mehler reaction and leads to oxidative stress (Greco, Chiappetta, Bruno, & Bitonti, 2012; Hanin et al., 2016; Mittler, 2002). It is reported that AMF symbiosis causes a fundamental change in physiology and biochemistry of the leaf and hydraulic properties of roots, which results in elevated photosynthesis, transpiration rate, and gaseous exchange (Hajiboland et al., 2010; Pedranzani et al., 2016; Porcel et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the global food production must sustainably increase with every increment in population. It is a disastrous stress, and around 7% of the world land is affected by high salt levels (Hanin, Ebel, Ngom, Laplaze, & Masmoudi, 2016; Hashem et al., 2016). As sodium chloride constitutes the majority of salts in affected areas, it is considered as a significant factor in causing salinization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point is underscored by the fact that our correlation coefficients were weaker than those found in most previous studies (Guo et al., 2010; Norden et al., 2009). The fact that we found a twofold variation in seed trait associations across the diverse habitats is certainly telling given that the correlations, although weak, were still significant (see Wang et al., 2014, 2016; Wu et al., 2013). …”
Section: Discussionmentioning
confidence: 99%